There's always vanilla - Drake, Jim; Gorn, Steve 1947- (capelight pictures, 2021)
"A young man returns to his home city of Pittsburgh and moves in with an older woman whom he begins to rely on for emotional and financial support." [imdb.com]
Original: USA 1971
Extras: "Affair of the heart" - Making-of ; Audiokommentar von Travis Crawford ; Location-Bildergalerie mit Kommentar von Lawrence DeVincentz ; Trailer
Bildformat 1.37:1 (1080p)
Keywords: Film